OPTIMIZATION OF PREOPERATIVE ASSESSMENT IN TRANSVAGINAL PELVIC RECONSTRUCTIVE PLASTIC SURGERY FOR THE TREATMENT OF PELVIC ORGANS PROLAPSE - S. V. Kamoeva; T. N. Savchenko; H. A. Abaeva; A. V. Ivanova (IRBIS LLC, 2016)
The objective of this study was to optimize the preoperative assessment in transvaginal pelvic reconstructive plastic surgery for the treatment of pelvic organs prolapse. Materials and methods: We conducted the quantitative and qualitative analysis of vaginal biocenosis in 68 female patients before and after administration of Polygynax. It was shown that Polygynax improves vaginal biocenosis owing to the reduction of microbial content. Therefore, the use of Polygynax for the preoperative assessment can be an effective method of prophylaxis of infectious and inflammatory complications and promote tissue regeneration after transvaginal pelvic reconstructive plastic surgery for the treatmentof pelvic organs prolapse.